Lineage-Specific Rewiring of Core Pathways Predating Innovation of Legume Nodules Shapes Symbiotic Efficiency - Wen-Jing Cui (American Society for Microbiology, 2021)
ABSTRACT The interkingdom coevolution innovated the rhizobium-legume symbiosis. The application of this nitrogen-fixing system in sustainable agriculture is usually impeded by incompatible interactions between partners. However, the progressive evolution of rhizobium-legume compatibility remains elusive. In this work, deletions of rhcV encoding a structural component of the type three secretion system allow related Sinorhizobium strains to nodulate a previously incompatible soybean cultivar (Glycine max). These rhcV mutants show low to medium to high symbiotic efficiency on the same cultivated soybean while being indistinguishable on wild soybean plants (Glycine soja). The dual pantranscriptomics reveals nodule-specific activation of core symbiosis genes of Sinorhizobium and Glycine genes associated with genome duplication events along the chronogram. Unexpectedly, symbiotic efficiency is in line with lineage-dependent transcriptional profiles of core pathways which predate the diversification of Fabaceae and Sinorhizobium. This is supported by further physiological and biochemical experiments. Particularly, low-efficiency nodules show disordered antioxidant activity and low-energy status, which restrict nitrogen fixation activity. Collectively, the ancient core pathways play a crucial role in optimizing the function of later-evolved mutualistic arsenals in the rhizobium-legume coevolution. IMPORTANCE Significant roles of complex extracellular microbiota in environmental adaptation of eukaryotes in ever-changing circumstances have been revealed. Given the intracellular infection ability, facultative endosymbionts can be considered pioneers within complex extracellular microbiota and are ideal organisms for understanding the early stage of interkingdom adaptation. This work reveals that the later innovation of key symbiotic arsenals and the lineage-specific network rewiring in ancient core pathways, predating the divergence of legumes and rhizobia, underline the progressive evolution of rhizobium-legume compatibility. This insight not only is significant for improving the application benefits of rhizobial inoculants in sustainable agriculture but also advances our general understanding of the interkingdom coevolution which is theoretically explored by all host-microbiota interactions.